Katherine Mansfield and Continental Europe Connections and Influences - Kimber, Gerri. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
This volume offers new interpretations of Katherine Mansfield's work by bringing together recent biographical and critical-theoretical approaches to her life and art in the context of Continental Europe. It features chapters on Mansfield's reception in several European countries together with her own translations of other European writers.